Seni Hadrah Sebagai Media Dakwah Dalam Membangun Syiar Islam di Masjid - Nur Laila Fitriani; Anjar Sulistyani (LPPM STIS Hidayatullah, 2022)
Islam always calls on the followers to be active spreading its values. People are attracted with Islamic of da’wah spreading through the art of Hadrah in Bohar Village, Taman District, Sidoarjo Regency, East Jawa. Da’wah is not only performed using printed or mass media, and preaching but also employing art. This study explores the Islamic value widespreading (syi’ar) utilising the art of Hadrah as da’wah media. The researcher analyses its roles and performances and reviews the obstacles of syi’ar at the mosque of Al Manshur. The research approach is descriptive qualitative which collect the data through interview and documentation. The finding shows that the mosque’s caretakers called Takmir and organisation of IPNU-IPPNU Ranting Bohar employs Hadrah to widespread the Islamic values as da’wah media. Hadrah has its roles with da’wah messages to impact the people and youth positively to recite and sing a religious chant praising Prophet Muhammada of sholawat. Hadrah connects good communication between Takmir and organisation of IPNU-IPPNU for a collaborative relation to create, develop, and spread the Islamic values at the mosque of Al Manshur.